Hydrallantois Associated with Fetal Anasarca in a Non-Descript Doe - singh, Sachan V; Yadava, CL; Gupta, RK; Saxena, A (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
A three years old goat in her 3rd parity was presented at full term without any signs of parturition along with bilateral tense abdominal distention (barrel like) since last 15 days. She was unable to bear body weight and reluctant to move since last 3 days along with labored breathing. Abdominal palpation and paracentesis of lower abdomen revealed the presence of huge amount of light amber colored watery fluid in uterus. Physiological parameters as temperature, heart rate and respiration rate and mucous membrane were 101.2°F, 86/min, 32/ min, and pink, respectively. There was a little reddish colored vaginal discharge since 2 days and on vaginal examination, cervix was found dilated. Based on history, symptoms, and clinical examination, the case was diagnosed as hydrallantois.